Measurement of Service Quality Using Single Truck Identification Data (STID) on Service User Satisfaction at the Main Port of Tanjung Perak Surabaya - Wardani, Widi Arum; Rakhman, Rizqi Aini; Yudianto, Prima Yudha; Rahayu, Trisnowati (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to measure how much the quality of service quality of the use of Single Truck Identification Data (STID) affects service users at Tanjung Perak Port. The research method used in this study is a quantitative research method, the population in this study is service users who use the Single Truck Identification Data (STID) card. The sampling technique used is the census technique, which is a sampling technique in which all members of the population are sampled. The results of the study showed that the quality of STID services had a significant influence on the level of satisfaction of service users, The results of the simple linear regression test showed a significance value of 0.000 (< 0.05) with a determination coefficient (R²) of 0.872, which means that 87.2% of service user satisfaction can be explained by the quality of STID services, while the rest was influenced by other factors that were not studied in this study. From the results of the descriptive analysis, most of the service quality indicators received high ratings from respondents.